Effect of Senior Secondary School Students’ Exposure to Formative Testing On Performance in Biology in Ekiti State, Nigeria - Adekunle T. Olutola, Henry O. Owolabi, (JCTE, 2023)
This is a pretest-posttest, quasi experimental study of the effects of formative testing procedures on Biology performance of senior secondary school students. Attempt was made to find out whether formative testing with remediation and without remediation across gender would affect the Biology performance of senior secondary school students. The 3 × 2 factorial design was adopted and a sample of 90 senior secondary school two (SSS 2) students consisting of forty-nine males and forty-one females was drawn.